2022
DOI: 10.3390/foods11213456
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha: Production and Microbiological Research

Abstract: Kombucha is a sparkling sugared tea commonly prepared using a sugared tea infusion and fermented at ambient temperature for several days using a cellulose pellicle also called tea fungus that is comprised of acetic acid bacteria and yeast. Consumption of Kombucha has been reported as early as 220 B.C. with various reported potential health benefits and appealing sensory properties. During Kombucha fermentation, sucrose is hydrolysed by yeast cells into fructose and glucose, which are then metabolised to ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 102 publications
(131 reference statements)
2
36
0
1
Order By: Relevance
“…A recent study by Lee et al 65 demonstrated that the main AAB found in several commercial kombucha SCOBY samples were Gluconobacter (95.25%) and Komagataeibacter (76.69%). The predominant LAB detected in kombucha primarily belonged to the Lactobacillus group, which enhances the biological function as probiotic kombucha beverages 66 , 67 . However, LAB were not detected in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Lee et al 65 demonstrated that the main AAB found in several commercial kombucha SCOBY samples were Gluconobacter (95.25%) and Komagataeibacter (76.69%). The predominant LAB detected in kombucha primarily belonged to the Lactobacillus group, which enhances the biological function as probiotic kombucha beverages 66 , 67 . However, LAB were not detected in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that the plant cell walls, such as those of the tea, contained high levels of insoluble bound phenols, which were difficult to release into the kombucha products. The beneficial metabolites produced by the microbial community during kombucha fermentation, such as acids, alcohols, and esters, can affect the solubility of the phenolic compounds, leading to the liberation of insoluble bound phenols 67 . As per the reduction in TPC seen in the kombucha products, the microbial community in the kombucha SCOBY can also release hydrolytic enzymes to degrade the polyphenols into other metabolites and use them as nutrient sources for metabolic activities, leading to a reduction in the TPC 6 , 84 , 85 .…”
Section: Resultsmentioning
confidence: 99%
“…The acetic acid bacteria (AAB) convert the two simple sugars to synthesize various organic acids and bacterial cellulose in the form of pellicle. Additionally, fructose could be metabolized by yeast into ethanol and carbon dioxide, the former being oxidized by Acetobacter into acetic acid, which are responsible for the acidity and functional activity such as microbial activity of kombucha [21,27]. Kombucha is known to produce various organic acids such as acetic, gluconic, glucuronic, malic, citric, tartaric, succinic, malonic, etc through fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Around 414 AD, Dr Kombu brought it from Korea to Japan, where it was appreciated for its properties in relieving digestive ailments. In the 20th century, it was brought to Eastern Europe from Russia, where it was known as “tea acid” [ 4 , 5 ]. The name kombucha is derived from Dr Kombu, and the cha part refers to tea in Japanese.…”
Section: Introductionmentioning
confidence: 99%